The The Dark Side of Village Governance: Analyzing the Paradoxical Effects of Discretion and Accountability on the Fraud Pentagon Model in Village Funds (A Study in Banawa Tengah District, Donggala Regency) - Muhammad Baihaqy Syam; Muhammad Ansar; Muhammad Din; Andi Ainil Mufidah Tanra; Lucyani Meldawati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Purpose: This study aims to examine the influence of discretion and accountability on fraud pentagon model practices in village fund management. The primary focus is to explore the interaction of these variables with the risk of fraud at the village level, testing the general assumption of whether these variables serve as preventive tools or, conversely, as facilitators. Methods: This study employs a quantitative approach with a sample size of 97 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), operated through SmartPLS 4 software. Results: The findings reveal significant yet paradoxical results. First, discretion has a positive and significant effect on fraud (0.445), indicating a loophole for the abuse of authority (opportunity). Second, accountability also has a positive and significant effect on fraud (0.504), demonstrating a phenomenon of "symbolic accountability" where administration is utilized as a facade to conceal irregularities. Overall, these two variables contribute 54.1% to the variance of the fraud pentagon model in village funds. Implications: These results indicate that strengthening accountability that is merely formalistic without substantive oversight actually increases the risk of fraud. It is recommended that local governments tighten the boundaries of discretion (bounded discretion) and transition the oversight system from mere document audits to more stringent physical field verification.